A Case Study on Learning Difficulties and Corresponding Supports for Learning in cMOOCs | Une étude de cas sur les difficultés d’apprentissage et le soutien correspondant pour l’apprentissage dans les cMOOC - Li, Shuang; Tang, Qi; Zhang, Yanxia (Canadian Journal of Learning and Technology, 2016)
cMOOCs, which are based on connectivist learning theory, bring challenges for learners as well as opportunities for self-inquiry. Previous studies have shown that learners in cMOOCs may have difficulties learning, but these studies do not provide any in-depth, empirical explorations of student difficulties or support strategies. This paper presents a case study on student difficulties and support requirements at the beginning of a cMOOC. Content analysis of messages posted by learners and instructors in four main online course learning spaces including Moodle, blogs, Facebook and Twitter was conducted. Three questions are explored in this paper: (1) What kinds of difficulties do learners encounter at the beginning of a cMOOC?; (2) Which of these difficulties are typical for most learners?; and (3) How are these difficulties responded to and supported in the cMOOC environment? Based on the research results of this study, we provide some reflections on learning support for cMOOCs and a discussion of the research itself in the last part of the paper.Les cMOOC, qui s’appuient sur une théorie pédagogique connectiviste, soulèvent des défis pour les apprenants ainsi que des occasions de questionnement de soi. Des études préalables ont démontré que les apprenants des cMOOC peuvent connaître des difficultés d’apprentissage, mais ces études n’offrent pas d’exploration empirique en profondeur des difficultés des élèves ni des stratégies de soutien. Cet article présente une étude de cas sur les difficultés des élèves et les besoins de soutien au début d’un cMOOC. On a procédé à l’analyse du contenu des messages publiés par les apprenants et les instructeurs dans les quatre principaux espaces en ligne pour l’apprentissage, c’est-à-dire Moodle, les blogues, Facebook et Twitter. Cet article explore trois questions : (1) Quels types de difficultés rencontrent les apprenants au début d’un cMOOC?; (2) Parmi ces difficultés, lesquelles sont typiques pour la plupart des apprenants?; et (3) Comment réagit-on à ces difficultés et comment y remédie-t-on dans l’environnement du cMOOC? En nous appuyant sur les résultats de recherche de cette étude, nous offrons quelques réflexions sur le soutien pédagogique pour les cMOOC et une discussion sur la recherche elle-même dans la dernière partie de l’article.